Infrared transparent printing ink and application thereof in packaging bag
By using polyurethane-acrylic composite emulsion and nanofiller system in packaging printing inks, combined with microcapsule packaging technology, the infrared band absorption problem is solved, high light transmittance and color development effect is achieved, and the accuracy and safety of infrared detection are improved.
Patent Information
- Application Number
- CN202510520825.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2025-08-26
AI Technical Summary
Existing packaging printing inks have strong absorption of the infrared band, resulting in attenuation of infrared detection signals, affecting defect recognition sensitivity and flaw detection accuracy. In addition, traditional X-ray detection has the risk of ionizing radiation, making it difficult to meet the universal needs of civilian scenarios.
Polyurethane-acrylic composite emulsion is used as the film forming matrix, combining nanobarium fluoride and modified zinc sulfide filler, organic color paste is encapsulated through microcapsules, reducing infrared band absorption, improving light transmittance, and improving interface binding and dispersion through silane coupling agent modification.
It realizes high light transmittance in the infrared band while color development in visible light, improves the sensitivity and accuracy of infrared detection, meets commercial printing requirements, and avoids the risk of ionizing radiation from X-ray detection.
Smart Images

Figure CN120535989A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of printing materials, in particular to functional printing materials, and more particularly to infrared transparent printing ink and application of the ink on packaging bags. Background Art
[0002] With the breakthrough development of uncooled infrared imaging technology, infrared inspection equipment, thanks to its radiation-free, easy-to-use, and low-cost advantages, has gained widespread application in civilian fields such as food quality inspection, electronic component flaw detection, and pharmaceutical packaging inspection. However, existing packaging printing inks, which commonly contain carbon black and some metal oxide / complex pigments, have strong infrared absorption. This results in attenuation of the infrared detection signal for packaged products, severely reducing defect recognition sensitivity and flaw detection accuracy.
[0003] Currently, nondestructive testing primarily relies on a dual approach of X-ray and infrared technologies. However, X-ray equipment carries the risk of ionizing radiation, requires strict shielding, and has high maintenance costs, making it difficult to meet the universal needs of civilian applications. In contrast, while infrared testing offers significant advantages, it is limited by the infrared-blocking properties of traditional inks, forcing some industries to choose X-ray solutions at the expense of safety. While academic research has attempted to improve infrared transmittance by reducing pigment dosage or employing low-absorption resin matrices, these efforts often result in insufficient color saturation or degraded mechanical properties, making them unsuitable for commercial printing.
[0004] Therefore, there is an urgent need to develop a printing ink that has both high visible light color rendering and infrared transparency. Summary of the Invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an infrared transparent printing ink that develops color in the visible light band and has high transmittance in the infrared band, allowing infrared rays to penetrate so as to be suitable for infrared detection.
[0006] To achieve the above objectives, the present invention provides the following technical solutions: An infrared transparent printing ink comprising the following components in percentage by weight: Polyurethane-acrylic composite emulsion 42-60%; infrared transparent filler 23-35%; organic color paste 5-15%; additives 4-8%; The organic color paste is provided with a microcapsule shell, the solid content of the polyurethane-acrylic acid emulsion is 40%-50%, and the infrared transparent filler comprises nano-barium fluoride and nano-zinc sulfide in a mass ratio of 1:(1-5); The organic color paste contains sulfonic acid groups in its molecular structure.
[0007] Furthermore, the nano-barium fluoride is a cubic crystal with a particle size of 50-100 nm.
[0008] Furthermore, the surface of the nano zinc sulfide is modified by a silane coupling agent, and the modification rate is ≥85%.
[0009] Furthermore, the organic color paste includes sulfonated phthalocyanine blue and azo red, the substitution degree of sulfonic acid groups in the sulfonated phthalocyanine blue molecules is ≥3, and the azo red is coated with an anionic surfactant.
[0010] Furthermore, the microcapsule shell includes a polyvinyl alcohol shell, and the diameter of the microcapsule is 2-5 μm.
[0011] Furthermore, the auxiliary agent includes at least one of a dispersant, a UV stabilizer, a leveling agent, and a cross-linking agent.
[0012] The present invention further provides a method for preparing the above-mentioned printing ink, and the preparation steps are as follows: S1: Add ZnS nanopowder and silane coupling agent to ethanol solution, ultrasonically treat, centrifuge, wash and dry to obtain modified ZnS; S2: Mix sulfonated phthalocyanine blue with polyvinyl alcohol aqueous solution, add it to a high-pressure homogenizer for emulsification and dispersion, then add salt solution dropwise to the mixture until the cloud point, collect the microcapsules by centrifugation and dry them; S3: Add BaF2, modified ZnS and dispersant into a sand mill and grind until ≥90% of the particles in the powder have a particle size of ≤500 nm; S4: adding BaF2, modified ZnS, microcapsules and additives to the polyurethane-acrylic composite emulsion and transferring the mixture to a blender for mixing to prepare ink particles; S5: The ink particles are transferred to a vacuum degassing machine for negative pressure degassing treatment, and then the agglomerated particles are removed by sieving. Deionized water is added to the remaining ink particles to adjust the viscosity to 1800-2200 mPa·s.
[0013] Further, In S1, the amount of silane coupling agent is 1.5-2% of the mass of the ZnS nanoparticles, and the solid-liquid ratio reaches 1:10 after adding the ethanol solution; In S2, sulfonated phthalocyanine blue and polyvinyl alcohol aqueous solution (10 wt %) are mixed at a ratio of 1:1.5, the pressure of the high-pressure homogenizer is 80 MPa, and the emulsification and dispersion cycle is repeated for more than 3 times; In S3: the sand mill uses zirconium beads with a diameter of 0.3 mm and the grinding time is more than 3 hours; In the above-mentioned S4, the polyurethane-acrylic composite emulsion comprises 60-77.3% of polyurethane prepolymer; 23-35% of acrylic monomer; 0.5-1.5% of initiator; 2-4% of emulsifier; and 0.1-0.3% of pH regulator. In the S5, the sieve aperture is 75-150 μm.
[0014] Further, In the S1, the pH of the ethanol solution was adjusted to 5.0 using acetic acid during ZnS modification.
[0015] In said S3, the sand mill is connected to cooling water, and the cooling water temperature is ≤25°C.
[0016] The present invention also provides the use of the infrared-transparent printing ink on packaging and / or packaging labels. The ink can be used in the printing layer of composite films including polyethylene, polypropylene, biaxially oriented polypropylene, polyethylene terephthalate, polyamide, and the like, and optionally, in printed materials such as labels applied to packaging surfaces.
[0017] The advantages and beneficial effects of the present invention are: 1. By utilizing sulfonated organic colorants and microencapsulation technology, the colorant's absorption of the infrared wavelength range (800-1500nm) is significantly reduced while retaining visible light color rendering capabilities, achieving compatibility with a high color gamut and infrared transmittance exceeding 90%. The inks described in this invention do not contain infrared-absorbing and reflective particles such as carbon powder, divalent copper, divalent iron, and tetravalent zirconium, which are common in traditional inks, allowing infrared light to penetrate the ink.
[0018] 2. The composite system of nano-BaF2 and modified ZnS has a refractive index that closely matches that of the resin matrix, synergistically broadening the infrared transmission window and outperforming a single filler system. The PVA wall microcapsules precisely encapsulate the colorant, preventing direct contact between the colorant and filler, minimizing light scattering losses and preventing colorant migration during the printing process.
[0019] 3. ZnS is modified with silane coupling agent, the interfacial bonding strength is improved, and the dispersion uniformity and water resistance are significantly better than the unmodified system.
[0020] 4. The infrared transparent printing ink shown in the present invention can be used to print patterns, text, etc. on the surface of composite film packaging products such as polyethylene, polypropylene, polyester, and polyamide as seen in the prior art, and can also be used to print text on label paper affixed to the surface. It has good mechanical properties and can achieve a visible and three-dimensional schematic effect. At the same time, it can be penetrated by infrared rays and infrared flaw detection can be performed on composite films, packaging bags, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a flow chart of the method for preparing infrared transparent printing ink of the present invention; Figure 2 This is a diagram showing the effect of the infrared transparent printing ink of the present invention on a packaging label. DETAILED DESCRIPTION
[0022] The present invention provides an infrared transparent printing ink, the technical principle of which is as follows.
[0023] A polyurethane-acrylic composite emulsion serves as the film-forming matrix. The polyurethane (PU) in its molecular chain provides flexibility and substrate adhesion, while the acrylic (AC) hard segments enhance coating hardness and weather resistance. By adjusting the PU / AC ratio (60-77.3% PU + 23-35% AC), the refractive index of the resin (n≈1.48) is closely matched (Δn<0.1) with that of nano-barium fluoride (BaF2, n=1.47) and surface-modified zinc sulfide (ZnS, n=1.49). This close refractive index match significantly reduces Fresnel reflection losses at the filler-resin interface, achieving a transmittance of >90% in the 800-1000nm infrared band. The viscosity of the polyurethane-acrylic emulsion changes with shear rate. At high shear rates (such as during screen printing), the viscosity decreases, facilitating ink flow through the screen. At low shear rates (such as during post-printing sagging), the viscosity increases, preventing ink runoff. This unique rheological property enables the ink to have good operability and stability during the printing process.
[0024] Infrared light has a wavelength range of approximately 700 nanometers to 1 millimeter and is categorized into near-infrared, mid-infrared, and far-infrared. A material's transparency to infrared light generally depends on its band structure and lattice vibrations. If a material's band gap is larger than the energy of an infrared photon, the photon will not be absorbed.
[0025] Zinc sulfide (ZnS) nanoparticles were chosen as the ink filler here. They have a wide energy band gap of approximately 3.5-3.7 eV, corresponding to blue light absorption in the visible spectrum. Band gap absorption does not occur in the near-infrared and mid-infrared bands, resulting in transparency in these regions. Although absorption peaks may exist in certain mid-infrared bands, the inherently large band gap of ZnS at the nanoparticle scale and weak Rayleigh scattering have limited impact on infrared transparency. However, it is important to ensure that the nanoparticles are evenly dispersed in the ink to avoid aggregation, which can lead to enhanced scattering.
[0026] In addition, BaF2 (cubic crystal) has intrinsic high transmittance in the 8-12μm long-wave infrared region, while ZnS has a low scattering rate in the 1-5μm short-wave infrared region. The two can be compounded in a 1:(1-5) ratio to broaden the infrared window and cover the operating band of common infrared sensors (such as InGaAs detectors).
[0027] The π-π conjugated structure of traditional organic pigments (such as phthalocyanine blue and azo red) absorbs near-infrared light (700-1000 nm), resulting in reduced infrared transmittance. This invention overcomes this problem by modifying the pigment molecules with sulfonic acid groups. The specific mechanism is as follows: the strong electron-withdrawing property of the sulfonic acid group reduces the electron cloud density of the conjugated system, shifting the maximum absorption peak of the pigment to the visible light region (for example, from 680 nm to 620 nm for phthalocyanine blue), thereby reducing competitive absorption of the infrared light. Furthermore, the spatial arrangement of the sulfonic acid groups further inhibits intermolecular aggregation, preventing the broad-spectrum absorption caused by aggregation.
[0028] To further isolate the interaction between the pigment and the infrared filler, the technical solution adopted by the present invention also includes using polyvinyl alcohol (PVA) microcapsules to encapsulate the color paste. The PVA wall material (2-5μm) confines the pigment within the micron-sized capsule, preventing it from migrating to the filler-resin interface and reducing light scattering. At the same time, the hydrophilicity of PVA enables the pigment to be released in a directionally directed manner to the substrate surface during printing, ensuring color uniformity (ΔE<1.5).
[0029] The surface of the nano-ZnS is modified with a silane coupling agent (KH-570). The methoxy groups of the silane coupling agent hydrolyze and condense with the hydroxyl groups on the ZnS surface, forming Si-O-Zn covalent bonds. Simultaneously, the long-chain polyether groups of the silane coupling agent are compatible with the resin matrix, enhancing interfacial bonding. The modified ZnS has a zeta potential of -35mV in the resin, preventing filler agglomeration through electrostatic repulsion and ensuring a concentrated particle size distribution (D90 < 500nm). The silane coupling agent also adsorbs on the filler surface, reducing interfacial energy and minimizing deviations in filler dispersion uniformity after grinding.
[0030] Gradient grinding uses zirconium beads (0.3 mm) to gradually break down the filler. The sand mill runs at 1200 rpm and the cooling water temperature is ≤25°C. This prevents local overheating that could lead to pre-crosslinking of the resin or a crystal phase shift in the filler (e.g., ZnS transitioning from cubic to hexagonal phase). This grinding method gradually breaks down large filler particles into smaller ones, avoiding excessive grinding that could disrupt the filler's crystal structure or cause agglomeration. Furthermore, the lower grinding temperature prevents thermal changes in the filler's properties during the grinding process.
[0031] Microcapsules are prepared using high-pressure homogenization (80 MPa, three cycles) to force sulfonated phthalocyanine blue and PVA aqueous solution into a uniform emulsion. Under high pressure, the droplets fragment to submicron size (D50 ≈ 0.5 μm). Salting-out phase separation (with the addition of Na₂SO₄) then induces the PVA to precipitate the encapsulated pigment, forming complete microcapsules. The PVA concentration (10 wt%) and core material ratio (1:1.5) are adjusted to maintain a stable capsule diameter of 2-5 μm, compatible with the screen printing mesh size (75-150 μm).
[0032] The ink viscosity is precisely controlled to 1800-2200mPa·s (25°C) by adding deionized water. The pseudoplastic fluid behavior of the polyurethane-acrylic emulsion ensures that the viscosity decreases at high shear rates during printing (to facilitate screen passing) and returns to high viscosity at rest (to prevent sagging).
[0033] The present invention may also incorporate various processing aids, such as dispersants, UV stabilizers, leveling agents, and crosslinking agents, to address processing and other issues encountered during ink synthesis. Specifically, leveling agents can improve the surface tension of the ink, ensuring even spreading of the ink across the substrate during printing. Defoamers can eliminate bubbles in the ink, preventing them from affecting print quality and optical properties. Benzotriazole UV absorbers (such as Tinuvin 326) are preferred UV stabilizers, as they convert UV energy (280-400 nm) into heat through an excited-state proton transfer mechanism, protecting the pigment and resin from photodegradation.
[0034] The hydrophobic groups (aliphatic carbon chains) in the polyurethane segments and the crosslinker form a three-dimensional network that blocks water penetration, reducing the coating's water absorption to less than 2% (ASTM D570), ensuring the coating's water resistance. Furthermore, the crosslinked structure imparts excellent barrier properties, preventing the penetration of substances such as oxygen and water vapor, thereby extending the ink's lifespan. The microphase separation of the acrylic hard segment (Tg≈85°C) and the polyurethane soft segment (Tg≈35°C) imparts dimensional stability to the coating over a wide temperature range (-20°C to 120°C).
[0035] The following embodiments are further described in conjunction with the accompanying drawings and examples. The following embodiments are only used to more clearly illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention.
[0036] Example 1 An infrared transparent printing ink is composed of the following components in percentage by mass: 55% of a polyurethane-acrylic acid composite emulsion (solid content 45%); 30% of an infrared transparent filler (nano-barium fluoride:nano-zinc sulfide = 1:2); 10% of an organic color paste; and 5% of an additive.
[0037] Among them: the infrared transparent filler is cubic crystal nano BaF2 (particle size 70nm) and silane coupling agent modified nano ZnS (modification rate 88%).
[0038] The organic color paste is sulfonated phthalocyanine blue (sulfonic acid group substitution degree 4, microcapsule coating, shell material is polyvinyl alcohol, diameter 3μm).
[0039] The additives include: polycarboxylate ammonium salt dispersant 2%, benzotriazole UV stabilizer 1%, polyether modified siloxane leveling agent 1%, and carbodiimide crosslinking agent 1%.
[0040] The preparation steps are as follows: S1: Add 100 g ZnS nanopowder and 1.5 g silane coupling agent (KH-550) to 1 L ethanol solution (pH = 5.0, adjusted with acetic acid), ultrasonicate for 1 h, centrifuge and wash three times, and dry at 60 °C.
[0041] S2: Sulfonated phthalocyanine blue was mixed with 10 wt% polyvinyl alcohol aqueous solution at a ratio of 1:1.5, and the mixture was homogenized and emulsified three times at 80 MPa high pressure. 10% Na2SO4 solution was added dropwise until precipitation at the cloud point. The microcapsules were collected by centrifugation and dried in a vacuum at 40°C.
[0042] S3: Add BaF2, modified ZnS and dispersant into a sand mill (0.3 mm zirconium beads, cooling water at 20°C) and grind for 3.5 h until D90 ≤ 500 nm.
[0043] S4: Add fillers, microcapsule color paste and additives to polyurethane-acrylic emulsion (composition: polyurethane prepolymer 60%, butyl acrylate 30%, potassium persulfate 0.9%, sodium lauryl sulfate 3%, ammonia water 0.3%), and mix with a mixer at 800 rpm for 1 hour.
[0044] S5: vacuum degassing (-0.09 MPa, 30 min), sieve through 100 μm sieve, add deionized water to adjust the viscosity to 2000 mPa·s.
[0045] Example 2 An infrared transparent printing ink is composed of the following components in percentage by mass: 42% polyurethane-acrylic acid composite emulsion (solid content 45%); 35% infrared transparent filler (nano-barium fluoride:nano-zinc sulfide=1:1); 15% organic color paste; and 8% additives.
[0046] Among them: the infrared transparent filler is cubic crystal nano BaF2 (particle size 100nm) and silane coupling agent modified nano ZnS (modification rate 85%).
[0047] The organic color paste is sulfonated phthalocyanine blue (sulfonic acid substitution degree 3, microcapsule coating, shell material is polyvinyl alcohol, diameter 2μm).
[0048] The additives include: polycarboxylate ammonium salt dispersant 5%, benzotriazole UV stabilizer 2%, polyether modified silicone leveling agent 0.5%, and carbodiimide crosslinking agent 0.5%.
[0049] The preparation steps are as follows: S1: Add 100 g ZnS nanopowder and 2 g silane coupling agent (KH-550) to 1 L ethanol solution (pH = 5.0, adjusted with acetic acid), ultrasonicate for 1.5 h, centrifuge and wash three times, and dry at 60 °C.
[0050] S2: Sulfonated phthalocyanine blue was mixed with 10 wt% polyvinyl alcohol aqueous solution at a ratio of 1:1.5, and the mixture was homogenized and emulsified three times at 80 MPa high pressure. 10% Na2SO4 solution was added dropwise until precipitation at the cloud point. The microcapsules were collected by centrifugation and dried in a vacuum at 25°C.
[0051] S3: Add BaF2, modified ZnS and dispersant into a sand mill (0.3 mm zirconium beads, cooling water at 25°C) and grind for 4 h until D90 ≤ 500 nm.
[0052] S4: Add fillers, microcapsule color paste and additives to polyurethane-acrylic emulsion (composition: polyurethane prepolymer 60%, butyl acrylate 35%, potassium persulfate 1.5%, sodium lauryl sulfate 3.3%, ammonia water 0.2%), and mix with a mixer at 1200 rpm for 2 hours.
[0053] S5: vacuum degassing (-0.12 MPa, 60 min), passing through a 75 μm sieve, and adding deionized water to adjust the viscosity to 1800 mPa·s.
[0054] Example 3 An infrared transparent printing ink is composed of the following components in percentage by mass: 60% of a polyurethane-acrylic acid composite emulsion (solid content 40%); 31% of an infrared transparent filler (nano-barium fluoride:nano-zinc sulfide = 1:4); 5% of an organic color paste; and 4% of an additive.
[0055] Among them: the infrared transparent filler is cubic crystal nano BaF2 (particle size 50nm) and silane coupling agent modified nano ZnS (modification rate 90%).
[0056] The organic color paste is a sulfonated phthalocyanine blue and an anion-coated azo red in a mass ratio of 1:1 (the former has a sulfonic acid group substitution degree of 3, and the latter is treated with sodium dodecylbenzenesulfonate, coated with microcapsules, the shell material is polyvinyl alcohol, and the diameter is 3μm).
[0057] Additives include: polyacrylate dispersant 3%, hindered amine light stabilizer 2%, fluorocarbon leveling agent 1%, and aziridine crosslinker 1%.
[0058] The preparation steps are as follows: S1: Add 100 g ZnS nanopowder and 2 g silane coupling agent (KH-550) to 1 L ethanol solution (pH = 5.0, adjusted with acetic acid), ultrasonicate for 2 h, centrifuge and wash three times, and dry at 50 °C.
[0059] S2: Sulfonated phthalocyanine blue was mixed with 10 wt% polyvinyl alcohol aqueous solution at a ratio of 1:1.5, and the mixture was homogenized and emulsified at 80 MPa for 4 times. 10% Na2SO4 solution was added dropwise until precipitation at the cloud point. The microcapsules were collected by centrifugation and dried in a vacuum at 25°C.
[0060] S3: Add BaF2, modified ZnS and dispersant into a sand mill (0.3 mm zirconium beads, cooling water at 25°C) and grind for 4 h until D90 ≤ 500 nm.
[0061] S4: Add fillers, microcapsule color paste and additives to polyurethane-acrylic emulsion (composition: polyurethane prepolymer 75.4%, butyl acrylate 20%, potassium persulfate 0.5%, sodium lauryl sulfate 4%, ammonia water 0.1%), and mix with a mixer at 1200 rpm for 1 hour.
[0062] S5: vacuum degassing (-0.15 MPa, 60 min), sieve through a 150 μm sieve, and add deionized water to adjust the viscosity to 2200 mPa·s.
[0063] Example 4 An infrared transparent printing ink is composed of the following components in percentage by weight: 58% of a polyurethane-acrylic acid composite emulsion (solid content 50%); 23% of an infrared transparent filler (nano-barium fluoride:nano-zinc sulfide = 1:5); 15% of an organic color paste; and 4% of an additive.
[0064] Among them: the infrared transparent filler is cubic crystal nano BaF2 (particle size 100nm) and silane coupling agent modified nano ZnS (modification rate 86%).
[0065] Anion-coated azo red (treated with sodium dodecylbenzenesulfonate, microcapsule-coated, shell material is polyvinyl alcohol, diameter 5μm).
[0066] The additives include: 2% polycarboxylate ammonium salt dispersant and 2% hindered amine light stabilizer.
[0067] The preparation steps are as follows: S1: Add 100 g ZnS nanopowder and 2 g silane coupling agent (KH-550) to 1 L ethanol solution (pH = 5.0, adjusted with acetic acid), ultrasonicate for 2 h, centrifuge and wash three times, and dry at 50 °C.
[0068] S2: Sulfonated phthalocyanine blue was mixed with 10 wt% polyvinyl alcohol aqueous solution at a ratio of 1:1.5, and the mixture was homogenized and emulsified at 85 MPa for 4 times. 10% Na2SO4 solution was added dropwise until precipitation at the cloud point. The microcapsules were collected by centrifugation and dried in a vacuum at 25°C.
[0069] S3: Add BaF2, modified ZnS and dispersant into a sand mill (0.3 mm zirconium beads, cooling water at 25°C) and grind for 4 h until D90 ≤ 500 nm.
[0070] S4: Add fillers, microcapsule color paste and additives to polyurethane-acrylic emulsion (composition: polyurethane prepolymer 77.3%, butyl acrylate 20%, potassium persulfate 0.5%, sodium lauryl sulfate 2%, ammonia water 0.2%), and mix with a mixer at 1200 rpm for 1 hour.
[0071] S5: vacuum degassing (-0.12 MPa, 60 min), sieve through a 150 μm sieve, and add deionized water to adjust the viscosity to 2200 mPa·s.
[0072] The above examples were sprayed onto 20μm thick label paper and analyzed experimentally. The results are shown in the table below. Infrared transmittance and reflectance refer to the lower limit (transmittance) and upper limit (reflection) values, respectively, under continuous wavelength variation. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. An infrared transparent printing ink, characterized in that: Includes the following components by mass percentage: Polyurethane-acrylic composite emulsion 42-60%; infrared transparent filler 23-35%; organic color paste 5-15%; additives 4-8%; The organic color paste is provided with a microcapsule shell, the solid content of the polyurethane-acrylic acid emulsion is 40%-50%, and the infrared transparent filler comprises nano-barium fluoride and nano-zinc sulfide in a mass ratio of 1:(1-5); The organic color paste contains sulfonic acid groups in its molecular structure.
2. The infrared transparent printing ink according to claim 1, characterized in that: The nano-barium fluoride is a cubic crystal with a particle size of 50-100 nm.
3. The infrared transparent printing ink according to claim 2, characterized in that: The surface of the nano zinc sulfide is modified by a silane coupling agent, and the modification rate is ≥85%.
4. The infrared transparent printing ink according to claim 1, characterized in that The organic color paste comprises sulfonated phthalocyanine blue and azo red, the substitution degree of sulfonic acid groups in the sulfonated phthalocyanine blue molecules is greater than or equal to 3, and the azo red is coated with an anionic surfactant.
5. The infrared transparent printing ink according to claim 1, characterized in that: The microcapsule shell comprises a polyvinyl alcohol shell, and the diameter of the microcapsule is 2-5 μm.
6. The infrared transparent printing ink according to claim 1, characterized in that The auxiliary agent includes at least one of a dispersant, an ultraviolet stabilizer, a leveling agent, and a cross-linking agent.
7. A method for preparing the infrared transparent printing ink according to claim 1, characterized in that: The following steps are involved: S1: Add ZnS nanopowder and silane coupling agent to ethanol solution, ultrasonically treat, centrifuge, wash and dry to obtain modified ZnS; S2: Mix sulfonated phthalocyanine blue with polyvinyl alcohol aqueous solution, add it to a high-pressure homogenizer for emulsification and dispersion, then add salt solution dropwise to the mixture until the cloud point, collect the microcapsules by centrifugation and dry them; S3: Add BaF2, modified ZnS and dispersant into a sand mill and grind until ≥90% of the particles in the powder have a particle size of ≤500 nm; S4: adding BaF2, modified ZnS, microcapsules and additives to the polyurethane-acrylic composite emulsion and transferring the mixture to a blender for mixing to prepare ink particles; S5: The ink particles are transferred to a vacuum degassing machine for negative pressure degassing treatment, and then the agglomerated particles are removed by sieving. Deionized water is added to the remaining ink particles to adjust the viscosity to 1800-2200 mPa·s.
8. The method for preparing infrared transparent printing ink according to claim 7, characterized in that: In S1, the amount of silane coupling agent is 1.5-2% of the mass of the ZnS nanoparticles, and the solid-liquid ratio reaches 1:10 after adding the ethanol solution; In S2, sulfonated phthalocyanine blue and polyvinyl alcohol aqueous solution (10 wt %) are mixed at a ratio of 1:1.5, the pressure of the high-pressure homogenizer is 80 MPa, and the emulsification and dispersion cycle is repeated for more than 3 times; In S3: the sand mill uses zirconium beads with a diameter of 0.3 mm and the grinding time is more than 3 hours; In the above-mentioned S4, the polyurethane-acrylic composite emulsion comprises 60-77.3% of polyurethane prepolymer; 23-35% of acrylic monomer; 0.5-1.5% of initiator; 2-4% of emulsifier; and 0.1-0.3% of pH regulator. In the S5, the sieve aperture is 75-150 μm.
9. The infrared transparent printing ink according to claim 8, characterized in that: In the S1, the pH of the ethanol solution was adjusted to 5.0 with acetic acid during ZnS modification. In said S3, the sand mill is connected to cooling water, and the cooling water temperature is ≤25°C.
10. Use of the infrared transparent printing ink according to any one of claims 1 to 9 in composite film packaging products and / or packaging product labels.